Colorectal carcinogenesis in the Lynch syndromes and familial adenomatous polyposis: trigger events and downstream consequences - Pål Møller; Aysel Ahadova; Matthias Kloor; Toni T. Seppälä; John Burn; Saskia Haupt; Finlay Macrae; Mev Dominguez-Valentin; Gabriela Möslein; Annika Lindblom; Lone sunde; Ingrid Winship; et al. (Hereditary Cancer in Clinical Practice, 2025)
Abstract Carcinogenesis encompasses processes that lead to increased mutation rates, enhanced cellular division (tumour growth), and invasive growth. Colorectal cancer (CRC) carcinogenesis in carriers of pathogenic APC (path_APC) and pathogenic mismatch repair gene (path_MMR) variants is initiated by a second hit affecting the corresponding wild-type allele. In path_APC carriers, second hits result in the development of multiple adenomas, with CRC typically emerging after an additional 20 years. In path_MLH1 and path_MSH2 carriers, second hits lead to the formation of microscopically detectable, microsatellite unstable (MSI) crypts, from which CRC develops in about half of carriers over their lifetime, often without progressing through a diagnosable adenoma stage. These divergent outcomes reflect the distinct functions of. the APC and MMR genes. In path_MLH1 and path_MSH2 carriers, a direct consequence of stochastic mutations may be the occurrence of invasive growth before tumour expansion, challenging the paradigm that an invasive cancer must always have an non-invasive precursor. In contrast to other path_ MMR carriers, path_PMS2 carriers who receive colonoscopic surveillance exhibit minimal increase in CRC incidence. This is consistent with a hybrid model: the initial mutation may cause an adenoma, and the second hit in the wild-type PMS2 allele may drive the adenoma towards become cancerous with MSI. Since all mutational events are stochastic, interventions aimed at preventing or curing cancer should ideally target the initial mutational events. Interventions focused on downstream events are external factors that influence which tumour clones survive Darwinian selection. In Lynch Syndrome, surveillance colonoscopy to remove adenomas may select for carcinogenetic pathways that bypass the adenoma stage.